Practical Synthesis of Pent-4-yn-1-ol and Pent-4-en-1-ol from Tetrahydrofurfuryl Halides - Saito, Katsuya; Sawazaki, Tomoya; Furusawa, Osamu; Kosugi, Teruo; Kimura, Yoshikazu; Kirihara, Masayuki (Synthesis, 2023)
Pent-4-yn-1-ol was prepared in a high yield by the reaction of tetrahydrofurfuryl chloride with n-BuLi in t-BuOMe at 0 °C. Pent-4-en-1-ol was prepared in a high yield by either the reaction of tetrahydrofurfuryl chloride or tetrahydrofurfuryl bromide with lithium in tetrahydrofuran at temperatures from 0 °C to ambient temperature.
Keywords: pent-4-yn-1-ol; tetrahydrofurfuryl chloride; n-butyllithium; t-butyl methyl ether; pent-4-en-1-ol; tetrahydrofurfuryl bromide; lithium; tetrahydrofuran